2022
DOI: 10.5194/acp-22-3433-2022
|View full text |Cite
|
Sign up to set email alerts
|

Measurement report: Ice-nucleating particles active  ≥ −15 °C in free tropospheric air over western Europe

Abstract: Abstract. Ice-nucleating particles (INPs) initiate ice formation in supercooled clouds, typically starting in western Europe at a few kilometres above the ground. However, little is known about the concentration and composition of INPs in the lower free troposphere (FT). Here, we analysed INPs active at −10 ∘C (INP−10) and −15 ∘C (INP−15) that were collected under FT conditions at the high-altitude observatory Jungfraujoch between January 2019 and March 2021. We relied on continuous radon measurements to disti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
5
9
0
Order By: Relevance
“…The increased n INP post heat and peroxide treatment is an unexpected result given previous studies on treated soil dust measurements (Conen et al, 2011;Hill et al, 2016;O'Sullivan et al, 2014;Tobo et al, 2014). However, increases in IN activity after heat treatment have been reported previously for airborne Saharan desert dust and aerosol collected during Saharan dust intrusions (Boose et al, 2019;Conen et al, 2022), as well as SSA and precipitation (Martin et al, 2019;McCluskey et al, 2018a), and should be further investigated in future studies. An increase in IN activity after peroxide treatment has also been reported in a Himalayan dust sample (Paramonov et al, 2018).…”
Section: Characterization Of Inps In Aerosolsupporting
confidence: 57%
“…The increased n INP post heat and peroxide treatment is an unexpected result given previous studies on treated soil dust measurements (Conen et al, 2011;Hill et al, 2016;O'Sullivan et al, 2014;Tobo et al, 2014). However, increases in IN activity after heat treatment have been reported previously for airborne Saharan desert dust and aerosol collected during Saharan dust intrusions (Boose et al, 2019;Conen et al, 2022), as well as SSA and precipitation (Martin et al, 2019;McCluskey et al, 2018a), and should be further investigated in future studies. An increase in IN activity after peroxide treatment has also been reported in a Himalayan dust sample (Paramonov et al, 2018).…”
Section: Characterization Of Inps In Aerosolsupporting
confidence: 57%
“…Droplets thus produced can be smaller than 50 µm [ 45 ] and get lofted above a canopy [ 46 ], where they evaporate in the drier air [ 47 ] and enrich it with the INPs [ 48 , 49 ] that were initially contained in the splash droplets. Whatever the mechanism, the most likely source of INPs aerosolized by raindrops impinging on the canopy would be ice-nucleation active epiphytic microorganisms, most of which are heat sensitive and only some are moderately heat tolerant [ 20 ]. Heat-sensitive INPs washed by rain from canopies will mix on the ground with a probably much larger pool of INPs that themselves are very unlikely to be transported through and above the canopy of the tropical rainforest.…”
Section: Resultsmentioning
confidence: 99%
“…Droplets thus produced can be smaller than 50 µm [45] and get lofted above a canopy [46], where they evaporate in the drier air [47] and enrich it with the INPs [48,49] that were initially contained in the splash droplets. Whatever the mechanism, the most likely source of INPs aerosolized by raindrops impinging on the canopy would be ice-nucleation active [20].…”
Section: River Water and The Atmosphere Can Have Different Sources Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have confirmed that several kinds of atmospheric particles, including mineral dusts, carbonaceous particles, and biological species, can act as immersion INPs (Hoose and Möhler, 2012;Murray et al, 2012;Kanji et al, 2017, and references therein). When present at atmospherically relevant amounts in droplets, mineral dusts mostly catalyze supercooled aqueous droplet freezing below −15 • C (Hoose and Möhler, 2012, and references therein;Murray et al, 2012;Kanji et al, 2017, and references therein), while biological species, such as pollen, fungal spores, and viruses, generally exhibit immersion IN activ-ity below −5 • C and are fully activated below −10 to −20 • C (e.g., Chou, 2011;Conen et al, 2015;Polen et al, 2016;Kanji et al, 2017;Conen et al, 2022;Porter et al, 2022). The reported atmospheric immersion INP number concentration (N INP ) values were measured between −5 and −38 • C and were normally on the order of 10 −2 to 10 3 # L −1 (e.g., Rogers et al, 1998;DeMott et al, 2010;Chen et al, 2018;Porter et al, 2022).…”
Section: Introductionmentioning
confidence: 99%